Development and standardization of an English proficiency test for fourth year high school students of agricultural schools - Nartea, Remedios Valenton 1934-
An English Proficiency Test was developed and standardized to assess the English proficiency of graduating high school students of agricultural schools. The test was administered to 1,114 students randomly selected from 11 agricultural schools all over Luzon. The findings of the study showed that the test is valid in measuring the English proficiency of graduating high school students of agricultural schools and in predicting the examinees' performance in English 1 in college. However, the results of the study pointed out the difficulty of examinees on tests in listening and writing skills, in answering questions that elicit interpretative responses, and in associating language form to meaning, which imply that the students were not given sufficient learning activities to develop these skills.